A 3D flower-like Co/Ni bimetallic organic framework as an excellent material for electrochemical determination of quercetin. (29th March 2023) - Zheng, Shengbiao; Liu, Tianna; Zhang, Nini; Li, Liang; Zhu, Yanli; Zhang, Erhui; Tang, Jing; Guo, Jiahao
Abstract : A scheme of the fabrication of 3D flower-like CoNi-MOF nanosheets and their application in electrocatalytic oxidation of quercetin. Abstract : In this report, CoNi-bimetal metal–organic framework (CoNi-MOF) nanosheets with a three-dimensional (3D) flower-like hierarchical structure have been fabricated to modify a glassy carbon electrode and improve its efficiency for determination of quercetin. Scanning electron microscopy, X-ray photoelectron spectroscopy, N2 adsorption–desorption isotherms and impedance spectroscopy were used for the characterization of the CoNi-MOF. Under optimal electrochemical conditions, the anodic peak current measured around 0.44 V ( vs. SCE) increased linearly in two linear ranges: 0.05 to 1.0 μM and 1.0–20 μM with a sensitivity of 13.21 μA μM −1 cm 2 and 0.934 μA μM −1 cm 2, respectively. The excellent electrochemical performance might be attributed to the hierarchical structure, large specific surface area and enhanced electrical conductivity. Finally, the analytical utility of the CoNi-MOF sensor was evaluated by detecting quercetin in human plasma samples.